Business Communication based on Spiritualty - Pane, Zulfikar Ikhsan; Nuraryo, Imam; Ismail, Hanif; Rahmadani, Rina (Technium Sustainability, 2025)
Good business communication is often only seen from a monetary perspective, meaning that it only focuses on profits but its sustainability is often forgotten. A multinational company that must carry out business activities in various cultural areas that are different from the company’s country of origin. So you must care about communicating the company’s programs both in the form of product and service promotions and in other forms so that there are no business communication irregularities. To achieve this goal, it is necessary to have an additional variable, namely spiritual value. This study makes spiritual value as well as a novelty of research. As a result, there are three spiritual values that were agreed to be raised, namely honesty in conveying information, always considering the interests of others and not being arrogant and obliged to follow the norms and customs of the information recipient community for the sake of sustainability.